2β- and 16β-hydroxylase activity of CYP11A1 and direct stimulatory effect of estrogens on pregnenolone formation. Issue 150 (June 2015) - Mosa, A.; Neunzig, J.; Gerber, A.; Zapp, J.; Hannemann, F.; Pilak, P.; Bernhardt, R.
Highlights: Activation of CYP11A1-dependent cholesterol conversion in the presence of estrogens. Establishment of an Escherichia coli based whole-cell system for NMR analysis of novel CYP11A1 products. 2β-Hydroxylation of DOC and androstenedione, 6β-hydroxylation of testosterone and 16β-hydroxylation of DHEA by CYP11A1. Abstract: The biosynthesis of steroid hormones in vertebrates is initiated by the cytochrome P450 CYP11A1, which performs the side-chain cleavage of cholesterol thereby producing pregnenolone. In this study, we report a direct stimulatory effect of the estrogens estradiol and estrone onto the pregnenolone formation in a reconstituted in vitro system consisting of purified CYP11A1 and its natural redox partners. We demonstrated the formation of new products from 11-deoxycorticosterone (DOC), androstenedione, testosterone and dehydroepiandrosterone (DHEA) during the in vitro reaction catalyzed by CYP11A1. In addition, we also established an Escherichia coli -based whole-cell biocatalytic system consisting of CYP11A1 and its redox partners to obtain sufficient yields of products for NMR-characterization. Our results indicate that CYP11A1, in addition to the previously described 6β-hydroxylase activity, possesses a 2β-hydroxylase activity towards DOC and androstenedione as well as a 16β-hydroxylase activity towards DHEA. We also showed that CYP11A1 is able to perform the 6β-hydroxylation of testosterone, a reaction that has been predominantly attributed to CYP3A4. Our results are the first evidence that sex hormones positively regulate the overall production of steroid hormones suggesting the need to reassess the role of CYP11A1 in steroid hormone biosynthesis and its substrate-dependent mechanistic properties.